Ứng dụng máy tính trong chẩn đoán kỹ thuật ô tô - Cao, Trọng Hiền (Bộ Giáo dục và Đào tạo, 2013)
The results of reseach can be applied in technical service of road transport inorder to determine the quality of transport fastly and exactly to limit accidents of road tran sport.